(g-h)(x) = 2x+1 -(<span>x-2)
</span>(g-h)(x) = 2x+1 - x + 2
(g-h)(x) = x + 3
Answer:
24 x 35 = 840
Step-by-step explanation:
what............there’s no pic
Answer:
-4
Step-by-step explanation:
Adding 21 and -21 cancel each other out so you're left with -4
Answer:
8n + 46
Step-by-step explanation:
Combine like terms. First, simplify the signs. two negatives directly next to each other equals one positive:
- (-5n) = + 5n
30 + 5n + 16 + 3n = (30 + 16) + (5n + 3n)
(30 + 16) = 46
(5n + 3n) = 8n
8n + 46 is your answer.